ANALISA FAKTOR-FAKTOR PENENTU BUDGETARY SLACK PADA LEMBAGA SWADAYA MASYARAKAT (STUDI EMPIRIS DENGAN MENGGUNAKAN STRUCTURALEQUATION MODELING) - Wayan, Maria Eurelia (UI Scholars Hub, 2014)
This study aims to examine the determinants of budgetary slack on NGOs. Tests performed by using Structural Equation Modeling (SEM). This study found evidence that factors budgetary participation, accountability demands, information asymmetry, and the behavior of individual NGOs affect budgetary slack. Also found a correlation between budgetary participation, accountability demands, information asymmetry and the behavior of individual NGOs. This study uses a survey with 210 respondents of the unit of analysis is the individual directors and managers of NGOs.